LeucoDiff: mobile application for hematology students improve their skills in calculating the leukocyte formula - Alves, Daniel (2019)
This paper describes the study conducted to design, implement and evaluate the LeucoDiff mobile application, in terms of a tool to help hematology students and professionals learning or improving their competences in calculating the leukocyte formula. LeucoDiff also includes gaming features to motivate the students in the learning process. The application was evaluated with 25 hematology students using a database of 3494 images of blood samples, taken in optical microscopy, properly evaluated by a set of experts in the field (clinical pathologists).